Penggunaan Data Envelopment Analysis (DEA) dalam Pengukuran Efisiensi Bank Umum Syari'ah di Indonesia - Puspitasari, Anita; Purnomo, Didit; Triyono, Triyono (Universitas Islam Negeri Sunan Kudus, 2017)
The purpose of the research is to analayze efficiency level of Sharia Commercial Bank in Indonesia (Bank Mega Syariah, Bank Muamalat Indonesia, Bank Panin Dubai Syariah, Bank BNI Syariah, Bank BRI Syariah, and Bank Syariah Mandiri) 2014-2015 period. Data used in this research is secondary data taken from Financial Statement Publication issued by Otoritas Jasa Keuangan (OJK). This research uses input-output variable with Data Envelopment Analysis (DEA) Method.The result shows the difference of efficiency score for each Sharia Commercial Bank. Based on the calculacy using Data Envelopment Analysis (DEA) Method on BUSN Foreign Exchange of Sharia Commercial Bank in Indonesia only Bank Panin Dubai Syariah that has been succeeded with 100 percent of continuously efficiency during the research. The highest efficiency is experienced by Bank BNI Syariah and BRI Syariah because during the research they experienced inefficiency. During the research Bank Mega Syariah experienced efficiency three times on quarter March 2014, March 2015, and June 2015. Bank Muamalat Indonesia only experienced efficiency twice on quarter March 2014 and March 2015, beside that Bank Muamalat Indonesia experienced inefficiency. Bank Syariah Mandiri experienced efficiency twice on quarter March 2015 and quarter December 2015.